Modeling Thermal Effects of Pulsating Currents in Human Tissues: How to Prevent Necrosis - Angiolo Farina; Antonio Fasano; Fabio Rosso (Biophysica)
In certain clinical applications, pulsating currents are applied to specific body regions for therapeutic purposes. In this paper, we analyze the resulting thermal field to determine the optimal amplitude, period, and duration of these stimuli, ensuring that the temperature in the targeted tissue remains below the necrosis threshold.